A طبی و زیبائشی مقاصد کے لیے انسانی چربی کا استعمال: فقہ اسلامی کی روشنی میں تجزیاتی مطالعہ: Use of Human Fat for Medicinal and Cosmetic Purposes: An analytical study in the light of Islamic jurisprudence - irfan-saghir; Ahmad, Dr. Zaheer (MEI, 2023)
Abstract From the first day of human, it has been an effort to maintain himself in such a way that with the passage of time, there is no change in his health, beauty and external structure, which will end the refinement of his personality, or his health deteriorates to such an extent that he is unable to perform his duties. A review of Islamic teachings also reveals that looking beautiful, healthy and strong is not only permissible but also required by Sharia. This is the reason why the hadith of Sahih Muslim has clarified the meaning that in the eyes of Allah, a strong and powerful believer is better than a weak believer. Nowadays, because science, especially the medical world, has developed so much that things that could not be imagined a few decades ago are now more than imagined in the practical world. The same development has made it easier for a man to try and use artificial methods to maintain his beauty and attractiveness, one of which is the method of (Liposuction) and (Fat Injection). That in which excess human fat is removed, or excess fat is injected into a specific organ, especially the face, to enhance, refine, and create a more attractive appearance. Apart from this, there are some medical cases in which doing (Liposuction) or (Fat Injection) becomes compulsory because there is no other treatment option left. All the above cases are very common and popular nowadays, especially for beauty this type of graft is used a lot. In the article under review, an analysis of these three situations has been presented in the light of Islamic jurisprudence, whether those cases of transplantation in which fat is used have any scope in Islamic jurisprudence or is it against Sharia teachings? Is it proper to establish regular medical banks for any such cases like blood bank, bone bank and skin bank or is it not proper to establish such banks? These are all the questions that have been analyzed in this article in the light of the views of Islamic jurists.